1999
DOI: 10.1046/j.1365-2389.1999.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Management effects on forms of phosphorus in soil and leaching losses

Abstract: Summary We should know the effects of soil use and management on the contents and forms of soil phosphorus (P) and the resulting potential for leaching losses of P to prevent eutrophication of surface water. We determined P test values, amounts of sequentially extracted forms of P, P sorption capacities and degrees of P saturation in 20 differently treated soils and compared these data with leaching losses in lysimeters. One‐way analyses of variance indicated that most fractions of P were significantly influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 19 publications
7
66
3
Order By: Relevance
“…On the other hand, P loss was lower from P45/ FDE200 (T2) during the first year (1.36 kg ha -1 ) than the second year (2.54 kg ha -1 ). In other studies (Leinweber et al 1999;Turner & Haygarth 2000;Djodjic et al 2004), typical P leaching losses were similar to our P45 (T1) treatment (<1 kg ha -1 yr-1 ). The application of FDE in T2 and T3 treatments resulted in a two-to five-fold increase in P loss by leaching compared with the P45 treatment (T1).…”
Section: Influence Of Phosphorus Inputs On Annual Changes In Phosphorsupporting
confidence: 87%
“…On the other hand, P loss was lower from P45/ FDE200 (T2) during the first year (1.36 kg ha -1 ) than the second year (2.54 kg ha -1 ). In other studies (Leinweber et al 1999;Turner & Haygarth 2000;Djodjic et al 2004), typical P leaching losses were similar to our P45 (T1) treatment (<1 kg ha -1 yr-1 ). The application of FDE in T2 and T3 treatments resulted in a two-to five-fold increase in P loss by leaching compared with the P45 treatment (T1).…”
Section: Influence Of Phosphorus Inputs On Annual Changes In Phosphorsupporting
confidence: 87%
“…1 and 2). The results are comparable to a study by Leinweber et al (1999), in which they found that higher mean concentration of the most labile forms of P tend to occur in arable soils, and more residual (stable) P in soil under fallow or reafforestation. Cultivation and the application of P fertilizers are responsible for the decline in stable P and the higher amount of labile P in the green soil in our study.…”
Section: Tp and Plant Available P Concentrationssupporting
confidence: 84%
“…Soil texture was examined directly, showing that soils with high sand content were the most responsive to KHCO 3 treatment. The higher P solubility in sandy vs. clay soils (Leinweber et al, 1999) may explain the higher P release from sandy soils following KHCO 3 treatment in our study. For soils containing <50% sand, KHCO 3 treatment increased water-extractable P approximately threefold; the proportion increased to eightfold at 80% sand (Fig.…”
Section: Discussionmentioning
confidence: 57%